The interconnectedness of poverty, child and early pregnancy: the Dilemma of education stakeholders in supporting girls’ education in Senegal - Abuya, Benta; Muhia, Nelson; Gueye, Barrel; Fall, Ndeye Awa (CV. Inara, 2024)
The paper examines the interrelationship of poverty, early marriage, and early pregnancy in Senegal; the consequences of early marriage and pregnancy on school outcomes, and how do they differ by region. The study adopted a conceptual framework that hinges on Bronfenbrenner's ecological theory of development. Data is from qualitative interviews with 96 participants: six policymakers; 26 program actors: and 64 beneficiaries, including 32 parents and 32 adolescents in 2020. We found that poverty and social norms are inextricably linked to early marriage and early pregnancy. Overall, more work is needed to curb early marriage, child marriage, and female genital excision.